Contributions from the Second and Third Internal Gravity Modes for the Vertical Motion Response. - Julio Buchmann (Anuário do Instituto de Geociências, 2008)
In earlier papers of a series of real data integrations of the National Center for Atmospheric Research Community ClimateModel with tropical heat anomalies display regions of pronounced subsidence and drying located several thousand kilometers westwardpoleward of the heating for cases of tropical Atlantic heating and tropical east Pacifi c heating. This highly predictable sinking responseis established within the fi rst fi ve days of these integrations. The normal-modes of a set of adiabatic primitive equations linearizedabout a basic state at rest are used to partition model response into gravity-inertia and Rossby modes. The most important contributionfor the vertical motion response comes from the gravity modes added for all vertical modes. The principal emphasis is given upon thecontributions of the second and third internal vertical modes (with equivalent depths on the order of a fews hundred meters) for thevertical motion response.